Tuning Solid-State Fluorescence to the Near-Infrared: A Combinatorial Approach to Discovering Molecular Nanoprobes for Biomedical Imaging - Singh, Ajay; Lim, Chang-Keun; Lee, Yong-Deok; Maeng, Joon-ho; Lee, Sangyoup; Koh, Joonseok; Kim, Sehoon (American Chemical Society, 2013)
Dyes showing solid-state fluorescence (SSF) are intriguing molecules that can emit bright fluorescence in the condensed phase. Because they do not suffer from self-quenching. of fluorescence, nanoscopic dense integration of those molecules produces particulate nanoprobes whose emission intensity can be boosted by raising the intraparticle dye density. In spite of the potential promise for imaging applications demanding intense emission signals, their excitation and emission spectra are generally limited to the visible region where biological tissues have less transparency. Therefore, the SSF-based nanoprobes have rarely been applied to noninvasive in vivo imaging. Here we report a combinatorial chemistry approach to attain a high level of tissue transparency of SSF by tuning its excitation and emission wavelengths to the truly near-infrared (NIR) region. We built a dipolar arylvinyl (ArV) scaffold-based chemical library where the optical bandgap could be narrowed to the NIR above 700 nm by combinatorial modulation of the g-electron push-pull strengths. The ArV-aggregated nanoparticles (FArV NPs) with a colloidal size less than 20 nm were formulated using a polymeric surfactant (Pluronic F-127) and applied to bioimaging in cells and in vivo. We demonstrate that some of FArV NPs have truly NIR excitation and emission of SSF, capable of noninvasive in vivo imaging (efficient lymph node mapping and early diagnosis of tumor) in mouse models by virtue of bright solid-state NW fluorescence and high signal-to-background contrast (S/B approximate to 8) as well as facile circulation in the living body.
Keywords: AGGREGATION-INDUCED EMISSION; ORGANIC NANOPARTICLES; ENHANCED FLUORESCENCE; IN-VIVO; DERIVATIVES; LIGHT; FLUOROPHORES; BIOPROBES; SYSTEMS; PROBES